Deportability, Labour and Health in Canada’s Late Capitalism - Rivas-Sánchez, Hector Eloy (Carleton University, 2019)
This dissertation explores the political economy of the physical and mental illnesses that the migrant workers experience while living and working under conditions of illegality in Canada's late capitalism. The dissertation is divided into three parts. The first part locates four social determinants of health underpinning the structural vulnerability to which the Latin American undocumented workers are subjected in this particular context. The second part describes the mental and physical health illnesses that the undocumented workers develop while living and working in Canada without authorization, according to the type of industry they work in (1.—Multinational Corporations, 2.—Medium-size local industries and 3.—Underground workers' cooperatives) and to the type of work they do. The empirical evidence illustrates that the undocumented immigrants who work for medium-size local enterprises, those who have been affected by deportability and deportation, as well as those who lost their legal status after being engaged in refugee claimant applications, are more likely to develop the most dramatic forms of physical and mental health diseases, all linked to what is called here "short- term historical trauma." In contrast, undocumented workers who work for underground workers' cooperatives are more likely to report better physical and mental health outcomes. Cooperative labour, free time and social solidarity make this possible. Overall, this thesis indicates that --as explored in part three-- under the social conditions organized by late capitalism, social solidarity and engagement in non-waged cooperative labour constitute social mechanisms by which undocumented migrants can access to forms of refuge, care, solidarity and social recognition that partially emancipate them from illnesses, suffering and social death. This thesis is based on an ethnographic work that I carried out over 24 months in Montreal. During that period of time, I worked side by side with Latin American undocumented workers in slaughterhouses and meatpacking factories, construction and home renovation companies, employment agencies, and as industrial cleaner for multinational corporations, spaces where I carried out direct empirical observation in the points of production and conducted 47 in-depth interviews on illegality, labor and health. I also conducted ethnographic work in hospitals and deportation centers.